Moral discourse in Hume's philosophy - Lateef, Sally (Al-Adab Journal, 2023)
Hume was able to build his philosophy on the basis of the experimental method. The certainty he wanted to reach was through experience and sensory perceptions. As for the role of the mind, its job was to analyze the information that reaches us through sensory perceptions.Therefore, moral discourse relied on emotions and emotions on the basis that the moral emotion issued by any human being depends on an internal sense or feeling that nature has instilled in the human race.Virtue, for example, is everything that gives a person a feeling of approval, and vice, on the contrary, represents everything that gives him an unpleasant feeling. Thus, moral judgment - according to Hume's opinion - is not derived from the judgments of reason, because the judgments of reason determine what is.According to Hume, human knowledge is due to the mind’s perceptions, which consist of two types: (impressions and ideas). The first type represents perceptions that enter the mind and includes (feelings, emotions, and emotions). As for the second type, ideas are the faint images in thinking and reasoning that we form from impressions. Our human nature sends images of our sensory impressions to our thoughts, including our congenital thoughts, which are the result of images of our sensory impressions. This sense is imprinted with a certain effect that forms images of this impression, so we form the congenital idea.This is how the moral discourse was towards knowledge and reason. Moral principles are real and realistic and depend on direct sensory perception through which we distinguish between good and evil.As for his moral discourse towards religion, his view towards religion was one of atheism, as he believed in multiple gods.His discourse towards politics was represented in not relying on issues related to human nature and the realities of human society. He considered the idea of justice to be one of the moral virtues through which we can resolve the conflicts that exist in society and ensure the rule of order in it.